Evidence for Extrathyroidal Formation of 3-Iodothyronamine in Humans as Provided by a Novel Monoclonal Antibody-Based Chemiluminescent Serum Immunoassay - Hoefig, Carolin S.; Köhrle, Josef; Brabant, Georg; Dixit, Kashinath; Yap, Beng; Strasburger, Christian J.; Wu, Zida (The journal of clinical endocrinology and metabolism, 2011)
Context:Thyronamines are thyronergic metabolites of thyroid hormones. Lack of reliable and sensitive detection methods for endogenous 3-iodothyronamine (3-T1AM) has so far hampered progress in understanding their physiological action and role in endocrine homeostasis or pathophysiology of diseases.Objective:We characterized newly generated mouse monoclonal 3-T1AM antibodies and established a monoclonal antibody-based chemiluminescence immunoassay as a powerful tool for monitoring 3-T1AM levels in investigations addressing altered serum profiles and potential sites of origin and action of 3-T1AM in humans.Design and Setting:Our exploratory study on 3-T1AM serum levels in humans measured 3-T1AM concentrations in comparison with thyroid hormones.Patients or Other Participants:Thirteen adult healthy subjects, 10 patients with pituitary insufficiency, and 105 thyroid cancer patients participated.Interventions:Interventions included l-T4 withdrawal in patients with pituitary insufficiency as well as TSH-suppressive T4 substitution in thyroid cancer patients.Results:3-T1AM was reliably quantified in human serum and stable after storage at room temperature and 4 C overnight as well as after four freeze-thaw cycles. The median serum concentration in healthy subjects was 66 ± 26 nm. 3-T1AM was also detected in T4-substituted thyroid cancer patients. Although free T4 and T3 significantly decreased during T4 withdrawal, 3-T1AM levels remained constant for 6 d.Conclusion:Because higher 3-T1AM levels are detectable in T4-substituted thyroid cancer patients after thyroidectomy/radioiodine treatment compared with healthy controls, we concluded that 3-T1AM is mainly produced by extrathyroidal tissues. The serum profile during T4 withdrawal suggests either a long half-life or persisting 3-T1AM release into serum from intracellular thyroid hormone precursors or stores.